UPAYA MERINTIS DESA WISATA MELALUI PELATIHAN DAN PENDAMPINGAN MASYARAKAT DI DESA CARANGREJO KECAMATAN SAMPUNG KABUPATEN PONOROGO - Reni Albertin Putri; Nurisa Hardiyanti; Kiki Wijayanti (Universitas Negeri Surabaya, 2019)
Desa Carangrejo, Kecamatan Sampung, Kabupaten Ponorogo has various tourism potential, such as ricefields, plantations, mountains, and ancestral graves that can be used as icon in term of developing itstourism. Bulurejo as one of the hamlets in Desa Carangrejo has its potential as the central of tourismbecause the ancestral grave of the villages icon is located there. Besides, Dukuh Bulurejo alsocontinuously produces crops which becomes superior, such as banana, turmeric, and ginger. The methodused by Internship student of UM 2018 in purpose of making Desa Carangrejo to be tourism village is byimplementing village development assistance. The development stage is done in two ways: 1)implementing physical readiness, and 2) implementing potential development by providing training andassistance for communitys empowerment, also independence in developing villages potentials.Implementation of physical readiness stage is done in the form of giving street name, procurement ofstreet sign, direction sign leading to ancestral grave, and preparing thirty-tree (33) permanent bins that arelocated in some agreed points. Implementation of villages potential development stage is done bycultivating turmeric and ginger, producing natural soap, utilization banana leaves and bark that was foundand planted in many places but not utilized optimally. Training and assistance programs with the aim ofdeveloping villages potency was done in order to prepare the village to be the tourism village.